RESEÑA de: Marcos del Cano, Ana Maria. (coord.); Bioética, Filosofía y Derecho. Melilla: Centro Asociado de la UNED de Melilla, 2004 - Jorqui Azofra, María (Revista de Derecho de la UNED (RDUNED), 2006)
-